Analisis Kesalahan Siswa Kelas IX SMP Negeri 5 Palu Dalam Menyelesaikan Soal Cerita Panjang Busur Dan Luas Juring Berdasarkan Prosedur Newman Ditinjau Dari Gaya Kognitif - Elisabet Linda Mariana Kayan; Dasa Ismaimuza; Mustamin Idris; Anggraini Anggraini (Universitas Tadulako, 2025)
This study aims to analyze the errors of ninth-grade students at SMP Negeri 5 Palu in solving word problems involving arc length and sector area using the Newman procedure, from a cognitive perspective. The subjects in this study were 26 ninth-grade students in the 2024/2025 academic year. Subjects were recruited using the GEFT test. Data were analyzed using the Newman procedure to identify error types. Data collection techniques included the GEFT test, written tests, and interviews. The results showed that both FI and FD students made no errors in reading and understanding the problems. FI students were more thorough in the transformation and process skills stages, but experienced difficulties in the final writing due to time constraints. Meanwhile, FD students made errors in transformation and process skills, particularly in entering incorrect radius values ​​into formulas, as well as errors in the final writing. Cognitive style influenced the types of errors made by students. FI students were more able to solve problems independently, while FD students required more guidance.